MICROCIRCULATORY ISCHEMIA AND STATINS: LESSONS OF INTERVENTION CARDIOLOGY - An. A. Alexandrov; I. I. Tchukaeva (Рациональная фармакотерапия в кардиологии)
Review is devoted to the pathogenesis of microcirculatory ischemia. Microcirculatory dysfunction has been identified in different groups of patients including syndrome X, diabetes mellitus 2 type, coronary heart disease. In coronary patients after transluminal angioplasty microcirculatory dysfunction is the reason of phenomenon of “non-reflow”. In result the procedure of revascularization is less effective. Therapy by statins can be beneficial for patients with microcirculatory ischemia.